2022
DOI: 10.1002/mbo3.1262
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of insertion sequence elements in plasmids relating to mgrB gene disruption causing colistin resistance in Klebsiella pneumoniae

Abstract: Colistin is a last resort antibiotic for the treatment of carbapenemase producing Klebsiella pneumoniae. The disruption of the mgrB gene by insertion sequences (ISs) is a mechanism mediating colistin resistance. Plasmids encode mobilizable IS elements which integrate into the mgrB gene in K. pneumoniae causing gene inactivation and colistin resistance. The species prevalence of mgrB-gene disrupting insertion elements ISL3 (ISKpn25), IS5 (ISKpn26), ISKpn14, and IS903B present on plasmids were assessed. IS conta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…IS-medicated insertion was the main reason for mgrB inactivation (65.38% in this study). Furthermore, the IS types involved IS kpn14 (52.94%), followed by IS 903 (23.53%,), IS kpn26 (11.76%), and IS kpn18 (11.76%), consistent with previous reports ( 16 , 18 , 38 , 39 ). IS kpn14 was prevalent as the main mgrB -inserted type in our study, which might vary geographically, such as IS 5 -like in Italy and Switzerland ( 4 , 37 ) and IS kpn26 in Taiwan ( 16 ).…”
Section: Discussionsupporting
confidence: 91%
“…IS-medicated insertion was the main reason for mgrB inactivation (65.38% in this study). Furthermore, the IS types involved IS kpn14 (52.94%), followed by IS 903 (23.53%,), IS kpn26 (11.76%), and IS kpn18 (11.76%), consistent with previous reports ( 16 , 18 , 38 , 39 ). IS kpn14 was prevalent as the main mgrB -inserted type in our study, which might vary geographically, such as IS 5 -like in Italy and Switzerland ( 4 , 37 ) and IS kpn26 in Taiwan ( 16 ).…”
Section: Discussionsupporting
confidence: 91%
“…Mutation of mgrB gene was the basis for resistance most frequently encountered in our study (11 out of the total strains) and was induced by either ISKpn25 (n = 6), ISKpn26 (n = 1), or a missense mutation M27K (n = 4), predicted as deleterious by bioinformatics tools. Several recent studies have highlighted the pivotal role of ISs in contributing to the emergence of colistin resistance by disrupting the mgrB gene [ 19 , 20 , 21 , 30 , 31 , 32 ]. Our findings provide evidence that plasmid IncFIB(pQil) encodes ISkpn25, while the ISKpn26 element is associated with IncFIA(HI1) and IncR plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings provide evidence that plasmid IncFIB(pQil) encodes ISkpn25, while the ISKpn26 element is associated with IncFIA(HI1) and IncR plasmids. Fordham et al demonstrated similar connections between these IS elements and their companion plasmid families, with the exception of the relationship between ISKpn26 and IncFII(pHN7A8) plasmids [ 19 ]. The M27K mutation in the mgrB gene was also reported to mediate colistin resistance in a previous study [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inactivation of mgrB gene has been reported that leads to upgrade of the PhoP-PhoQ, which make for overexpression of the relevant operon and resistance to colistin [6]. At the same time, mutations in the above regulatory systems (pmrA, pmrB, pmrC, crrAB, mgrB and phoP/phoQ) have also been shown to be associated with colistin resistance [7].…”
Section: Introductionmentioning
confidence: 99%